BIODIESEL PRODUCTION FROM THORN APPLE (DATURA METEL) SEEDS OIL USING NAOH AS CATALYST - MUHAMMAD, CHIKA; UBA, AHMAD; MUKTAR, MUHAMMAD; OPOTU, MUK OTARU ADAMS OPOTU; AGADA, FRANCIS; MUHAMMAD, ABUBAKAR UMAR; ALHASSAN, YAHAYA; ADAMU, ABUBAKAR USMAN; AHMED, ABDULLAHI B. (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2019)
The oil used in this work was extracted from the seeds of Datura metel commonly called Thorn apple, Devils weed. 650ml of the oil extract was obtained by using soxhlet extraction and n-hexane as solvent the physico-chemical properties of the oil were evaluated. Two-step Transesterification of the oil in the presence of NaOH as catalyst was done by varying catalyst concentration as 1 %, 2 % of the weight of the oil with 6:1 and 9:1 molar ratio of methanol to oil at constant reaction temperature (60 0C) and time (120 mins). The biodiesel yields maximally (80 %) at 1 % catalyst (NaOH) concentration with 6:1 molar ratio of the methanol to oil. Acid value, Free Fatty acid, saponification value, iodine value and the moisture content of the biodiesel produced were 4.21 mg KOH/g, 2.10 %, 56.1 mg KOH/g, 22.84 g I2/100g and 3.0 % respectively. The cetane number, higher heating value and flash point were determined given at 138.451, 49.09 KJ/Kg, and 146 0C which are in agreement with the ASTM standard for determining biodiesel properties suitable for diesel engines. The 14.3 % yield of the oil from Datura metel seeds makes it a good feedstock for biodiesel production, hence a viable source of renewable energy for future use.